Questionnaire instrumentation for strategic vocabulary learning in the Swedish as a second language learning context - LaBontee, Richard (Studies in Second Language Learning and Teaching, 2019)
This article reports on the final round of piloting for a questionnaire instrument created and designed with the intention of collecting self-report data on adult, beginner Swedish L2 learners’ use of vocabulary learning strategies. The Swedish Vocabulary Learning Strategy Survey (SVLSS) version 1.2 is distributed to 182 participants studying Swedish at institutes of higher learning in Sweden. The collected data set is subject to exploratory factor analysis to explore initial interpretations of the underlying constructs of the instrument, and analyzed for content validity and internal consistency. Readability and accessibility of the instrument is also addressed. Initial findings and interpretations are used to guide the development of a preliminary VLS taxonomy for the SVLSS, as well as suggest and perform revisions that will result in the SVLSS 2.0.